2020
DOI: 10.1186/s40643-020-00303-z
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in silico antioxidant and antiproliferative activity of rhizospheric fungus Talaromyces purpureogenus isolate-ABRF2

Abstract: The present study evaluated the potential biological activities of rhizospheric fungi isolated from the Achanakmar Biosphere Reserve, India. Fungus, Talaromyces purpureogenus isolate-ABRF2 from the soil of the Achanakmar biosphere was characterized by using morphological, biochemical and molecular techniques. Fungus was screened for the production of secondary metabolites using a specific medium. The metabolites were extracted using a suitable solvent and each fraction was subsequently evaluated for their anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Rhizospheric fungi were collected from the rhizospheric region of soil from the Achanakmar Biosphere (Bilaspur) in the central mainland of the Indian subcontinent renowned as "Herbal State-Chhattisgarh" by the method of (Radhika and Rodrigues 2010). The fungus was identified and characterized as described previously by (Sahu et al 2020).…”
Section: Fungal Isolation and Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Rhizospheric fungi were collected from the rhizospheric region of soil from the Achanakmar Biosphere (Bilaspur) in the central mainland of the Indian subcontinent renowned as "Herbal State-Chhattisgarh" by the method of (Radhika and Rodrigues 2010). The fungus was identified and characterized as described previously by (Sahu et al 2020).…”
Section: Fungal Isolation and Identificationmentioning
confidence: 99%
“…Recent studies showed several bioactive compounds, including antifungal and antibacterial agents, have been isolated from fungi (Sahu et al 2020). The promotion of plant growth is the significant contribution of fungal symbiosis.…”
Section: Introductionmentioning
confidence: 99%
“…The column purified fractions containing secondary metabolites from YESB extract were also tested for antimicrobial activity based on inhibition of growth of B. Cerculans , B. Subtilis , E. coli , S. Aureus and Ralstonia eutropha (MTCC-2487), (Sahu et al, 2020) at a maximum concentration of 100µg/mL for qualitative assay (Fig. 10 and Table 2).…”
Section: In Vitro Antimicrobial Activity Of Potent Fungusmentioning
confidence: 99%